Steel for offshore wind turbines of class 46 kg with high modulus of elasticity and method for its production
Patent Information
- Application Number
- CN202611375348.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-09
AI Technical Summary
[0013]1、目前已公开的高弹性模量钢技术方案多采用高合金元素、金属间化合物及复杂粉末冶金工艺,增加了材料的制造成本,难以适应海上风电装备大批量生产需求
[0049](1)本发明通过采用低C、Mn+“Ni-Cu-Mo”耐海水全浸腐蚀合金化+“Ti-B”原位析出增强相+Nb微合金化的成分设计,在低C、低Mn体系保证高铁素体比例和良好的塑性储备基础上,控制1.05%≤Ni+Cu+Mo≤1.85%、2.0≤(Ni+Cu)/Mo≤4.5以形成稳定、均匀的复合耐蚀锈层,并通过Nb微合金化细化组织。
Smart Images

Figure CN122879609A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of medium and thick steel plates, and particularly relates to a 46kg grade structural steel for offshore wind power with high elastic modulus and resistance to seawater immersion corrosion, and its manufacturing method. Background Technology
[0002] As an emerging industry for achieving green energy transformation and high-quality development, offshore wind power is rapidly expanding its installed capacity and application scenarios to deep and remote seas. Compared to onshore wind power, offshore wind power equipment faces more complex natural environments and more stringent structural safety challenges during service, including the combined effects of strong wind loads, wave impacts, hydrodynamic interference, sea ice loads, tidal forces, and long-term corrosion from multiple sources. These external environmental conditions require wind turbine structures to possess higher stiffness control capabilities, deformation stability, and operational reliability throughout their entire lifecycle. With the continuous increase in the power of offshore wind turbines and the expansion of their overall size, the total tower height of megawatt-class wind turbines often exceeds 140 meters, the hub center height continues to rise, and the rotor diameter even exceeds 120 meters. This massive structural system needs to maintain overall coordinated deformation and local vibration resistance under multi-axis coupled loads to avoid structural instability such as resonance, instability, or stress concentration failure. This complex dynamic behavior places higher demands on the stiffness properties of materials, especially the elastic modulus.
[0003] The elastic modulus is a fundamental parameter that measures a material's ability to undergo elastic deformation under unit stress, directly determining the stiffness level and first-order natural frequency of structural components. In critical structures such as wind turbine towers, jacket structures, and pile foundations, increasing the material's elastic modulus not only helps control overall deformation but also effectively raises the structure's natural frequency, reducing the risk of resonance between wind-induced and wave-induced excitation and the structure's natural modes. This reduces fatigue accumulation effects and vibration amplitude, extending service life. Furthermore, high-elastic-modulus steel can also offer significant cost-saving and efficiency-enhancing potential by reducing structural wall thickness or increasing stiffness per unit mass. However, the elastic modulus is an intrinsic property of a material, primarily determined by interatomic bonding forces and crystal structure. Traditional alloy composition design, rolling, or heat treatment processes cannot significantly alter this intrinsic property of steel. Therefore, the difficulty in achieving stiffness enhancement with traditional wind power steel has become one of the core factors restricting the optimization of wind power equipment structural design.
[0004] Currently, structural steels widely used in engineering practice, such as Q420, Q460, and their derivatives, while meeting basic structural requirements in terms of strength and toughness, generally have an elastic modulus between 200 and 210 GPa. This is significantly different from the increasingly stringent high stiffness requirements of wind power structures, making it difficult to meet the differentiated control of modulus levels in design. Especially in wind power structures, different parts have different load-bearing conditions and deformation requirements, necessitating the use of a series of structural steels with higher modulus levels that simultaneously meet yield strength and processing adaptability requirements. This is to achieve overall stiffness matching, structural response coordination, and expanded design optimization space.
[0005] Currently, relevant domestic and international standards such as GB / T1591 "Low-alloy High-strength Structural Steel", GB / T712 "Structural Steel for Shipbuilding and Marine Engineering", EN10025, and EN10225 have provided general strength grades of steel foundations for wind power structures. However, a systematic design and material matching system has not yet been formed for stiffness performance indicators. The lack of systematic optimization and clear constraints on the elastic modulus parameter in existing material systems limits further improvements in high-order dynamic response control, overall stiffness enhancement, and stability under ultimate loads for wind power structures.
[0006] In summary, developing a series of wind turbine structural steels with high elastic modulus and excellent comprehensive mechanical properties has become an urgent need for the current development of offshore wind power equipment materials technology. By constructing a series of high elastic modulus steel products ranging from low to high strength grades, and configuring material performance according to the strength and stiffness requirements of different structural parts such as the upper transition section of various offshore wind turbines, maintenance platform supports, pile foundation uppers, pile foundation nodes, X-joints, suction cylinders, jacket structures, and tendon tubes, it is possible to significantly improve structural response control capabilities, enhance service stability, and provide key material support for offshore wind power equipment to move towards higher power, larger scale, and farther sea areas. The construction of this material system will play a vital role in improving the operational reliability and industrial competitiveness of offshore wind power equipment.
[0007] Public reports on related patents:
[0008] Chinese invention patent CN114686783B discloses a high-elasticity modulus age-hardening high-speed steel material and its preparation method. It employs a multi-element high-alloy system, using solid solution strengthening by adding Cr, V, Ni, and the non-metallic element N, as well as synergistic particle reinforcement by adding nitrides. Combined with powder metallurgy + high-temperature solid solution + aging treatment processes, a high-elasticity modulus age-hardening high-speed steel with an elastic modulus greater than 240 GPa is obtained. This method uses high-temperature heat treatment to form a dispersed phase to enhance stiffness, making it suitable for the cutting tool and mold fields. However, due to its primary use of powder metallurgy, its complex composition, high processing temperature, and high cost make it difficult to meet the engineering adaptability requirements of wind power structural steel in large-scale continuous casting-hot rolling production and low-cost manufacturing.
[0009] Chinese invention patent CN108265226A discloses a method for manufacturing offshore wind power steel with a yield strength ≥460MPa. It employs a C-Si-Mn-Al-Nb-V-Ti-Ni-Mo system and a controlled rolling and cooling process to obtain steel for offshore wind turbine tower structures with a yield strength ≥460MPa, tensile strength 550~720MPa, and elongation A ≥25%. This approach emphasizes the strength, toughness, and low-temperature service adaptability of the 460MPa grade offshore wind power steel, but does not use the elastic modulus as a design indicator for the stiffness and modal response of the wind power structure, nor does it propose a design mechanism for in-situ generation of high-modulus reinforcing particles.
[0010] Chinese invention patent CN113913690A discloses a steel for offshore wind turbine flanges and its preparation method. It employs a C-Si-Mn-Cr-Cu-Ni-V-Nb-RE composition system, achieving a yield strength ≥460MPa, tensile strength 530~680MPa, Z35 grade thickness-direction properties, and -60℃ low-temperature impact resistance. This solution focuses on addressing the corrosion resistance, low-temperature resistance, weldability, and resistance to lamellar tearing of the steel for offshore wind turbine flanges. However, it does not address the Ni-Cu-Mo proportional corrosion-resistant design under full seawater immersion conditions, nor does it propose improving the material's elastic modulus by introducing reinforcing phases.
[0011] Chinese invention patent CN111809117B discloses a high fracture toughness and low aging sensitivity offshore wind power steel and its production method. It employs a C-Si-Mn-Nb-Ti-Mo-Ni composition system and achieves excellent CTOD and low-temperature aging performance through a process path of continuous casting + two-stage controlled rolling + UFC / ACC controlled cooling + hot straightening + stacking cooling. While this solution focuses on improving the safety of welded joints and service aging stability, and significantly controls microstructure and toughness, it does not propose a design mechanism to increase the material's elastic modulus to enhance structural stiffness.
[0012] In summary, current high-elasticity modulus steel and offshore wind power steel, as well as their manufacturing technologies, have the following shortcomings:
[0013] 1. Currently, most publicly available high-elasticity modulus steel technologies employ high alloying elements, intermetallic compounds, and complex powder metallurgy processes, which increases the manufacturing cost of materials and makes it difficult to meet the needs of mass production of offshore wind power equipment.
[0014] 2. Existing high elastic modulus steels do not involve the service performance required in marine environments, such as low-temperature impact toughness and corrosion resistance. They are difficult to meet the thickness specifications of large offshore wind power structural components, and it is also impossible to evaluate the service safety of materials in marine environments.
[0015] 3. Existing research on offshore wind power steel and marine engineering structural steel of similar strength grade mainly focuses on strength, low temperature toughness, Z-direction performance, weldability, ductility or production stability of thick specifications. The modulus of elasticity has not yet been used as a clear material indicator for the stiffness and modal response of wind power structures. This makes it difficult to meet the structural safety and stiffness requirements brought about by the further development of offshore wind power equipment towards deep sea, high power and large size. Summary of the Invention
[0016] The purpose of this invention is to overcome the above-mentioned problems and deficiencies and provide a 46kg-grade offshore wind power steel with a high elastic modulus, excellent resistance to seawater immersion corrosion, good low-temperature toughness and elongation, suitable for underwater structures such as floating wind turbine tendons, underwater compartments, and outer plates of pontoons / buoy boxes, and its production method. The steel has an elastic modulus ≥220GPa, yield strength ≥460MPa, tensile strength 550~720MPa, elongation after fracture ≥21%, Charpy impact energy ≥150J at -20℃, excellent resistance to seawater immersion corrosion, and good low-temperature toughness and elongation.
[0017] The objective of this invention is achieved as follows:
[0018] A 46kg grade offshore wind power steel with high elastic modulus has the following composition by weight percentage: C: 0.035%~0.045%, Si: 0.20%~0.30%, Mn: 0.80%~0.90%, Ni: 0.50%~0.90%, Mo: 0.30%~0.50%, Cu: 0.25%~0.45%, Nb: 0.040%~0.060%, Ti: 1.50%~2.50%, B: 0.60%~1.20%, Ca: 0.0010%~0.0030%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities.
[0019] Furthermore, in the wind power steel, -0.4%≤Ti-2.22×B≤0.4%.
[0020] Furthermore, in the wind power steel, 1.05%≤Ni+Cu+Mo≤1.85% and 2.0≤(Ni+Cu) / Mo≤4.5.
[0021] Furthermore, the microstructure of the wind power steel includes ferrite and bainite, with fine TiB2 hard reinforcing particles uniformly dispersed throughout the steel.
[0022] Furthermore, the ferrite volume percentage is 75%~85%, and the average ferrite grain diameter is <11μm; the TiB2 hard reinforcing particles in the wind power steel have a volume fraction >3%, an average particle size <3μm, and a distribution density of 2000~3000 particles / mm. 2 .
[0023] The steel plate used for offshore wind power has an elastic modulus ≥220GPa, yield strength ≥460MPa, tensile strength 550~720MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥150J, and a steel plate thickness of 20~40mm.
[0024] The rationale for the design of the components in this invention is as follows:
[0025] The overall design concept of this invention is as follows: First, focusing on the coupled requirements of rigidity, low-temperature toughness, and resistance to full seawater immersion corrosion of medium-thick steel plates such as 46kg-class offshore floating wind turbine tendon tubes, underwater compartments, and outer plates of pontoons / buoy boxes, the steel plate composition adopts a low C and Mn content design. The low C and Mn system ensures the ferrite phase ratio in the final microstructure of the steel plate, compensating for the plasticity loss caused by the introduction of hard reinforcing phase particles; Second, the addition of Ni, Cu, and Mo composite corrosion-resistant elements is increased and controlled at 1.05%≤Ni+Cu+Mo≤1.85% and 2.0≤(Ni+Cu) / Mo. The presence of Ni-rich spinel, Cu oxide, and Mo oxide / molybdate stabilizes a dense internal rust layer, enhancing corrosion resistance in fully immersed seawater environments and extending the service life of offshore wind power steel. Furthermore, Nb microalloying significantly inhibits austenite grain growth and promotes ferrite refinement, thereby improving the overall strength, toughness, and microstructure uniformity of the steel plate. Finally, the introduction of Ti and B elements into a low-carbon corrosion-resistant matrix, controlled by the Ti-B ratio of -0.4%≤Ti-2.22×B≤0.4%, ensures that the reinforcing phase forms in situ and remains fine and dispersed during the solidification of the molten steel and subsequent solidification microstructure evolution. High-modulus particles constrain composition, inclusions, solidification flow, rolling deformation, and phase transformation microstructure to achieve elastic modulus gain under 46kg-level strength, toughness, and corrosion resistance conditions, meeting the high-rigidity steel plate requirements of large-scale offshore wind power structural designs.
[0026] Carbon (C) is one of the fundamental elements ensuring the strength of the steel plate matrix. Although this invention uses a low-carbon system, C can still synergistically enhance the strength of the steel plate through solid solution strengthening and microalloying precipitation strengthening mechanisms. In this invention, the design role of C content is mainly reflected in the following three aspects: First, it contributes to the strength of the steel plate matrix through solid solution strengthening; second, it provides the necessary carbon source for the formation of NbC precipitates by working together with microalloyed Nb elements, thus pinning grain boundaries in the form of NbC precipitation to hinder austenite grain coarsening and providing favorable conditions for final microstructure refinement control; third, based on the perspective of phase structure control, it adopts the lowest possible C content to increase the proportion of soft ferrite phase, thereby compensating for the plasticity problem caused by the introduction of elastic modulus-enhancing phase particles. Therefore, considering the purpose of the invention and the overall performance, the preferred C content is controlled at C: 0.035%~0.045%.
[0027] Si is the main deoxidizing component in the steelmaking process. Si in solid solution form can increase strength, ductile-brittle transition temperature, elastic limit and fatigue strength. In order to obtain sufficient deoxidation effect, it must contain more than 0.10%. However, if the upper limit is too high, it will reduce the toughness of the base material and welded parts and have an adverse effect on the surface quality of the steel. Therefore, it is preferred to control the Si content at 0.20%~0.30%.
[0028] Mn: Mn is an essential element for ensuring the strength and toughness of steel. In this invention, the role of Mn is mainly reflected in two aspects: first, it contributes to the strength of the steel plate matrix through solid solution strengthening; second, Mn expands the austenite region, which can improve the hardenability of steel and facilitate the bainite transformation of the steel plate during the ACC rapid cooling process of the manufacturing method of this invention. However, Mn is prone to segregation in steel, and in medium and thick plates, it is easy to produce compositional segregation and banded structure, especially at 1 / 4 and 1 / 2 thickness, which can cause low-temperature toughness fluctuations and fracture delamination tendency; moreover, the increase of Mn content increases Ceq, worsens the sensitivity to weld cracking, and weakens the formation stability of protective rust layer in the Cl--containing marine environment, which is not conducive to corrosion resistance; therefore, considering the material mechanics and corrosion resistance properties, the preferred Mn content range is controlled between 0.80% and 0.90%.
[0029] Ni: Ni is an effective element for improving the stability and low-temperature toughness of rust layers under seawater immersion corrosion. During corrosion, Ni can participate in the Fe3O4 spinel structure to form Ni-rich spinel or NiFe2O4, improving the density and Cl- barrier capacity of the inner rust layer, shifting the corrosion potential of the steel matrix positively, and reducing the corrosion rate. Simultaneously, Ni can improve low-temperature impact toughness and synergistically reduce copper embrittlement and surface crack sensitivity of Cu-containing steel during hot working. When the Ni content is too low, the stabilizing effect of Ni-rich spinel on the rust layer is insufficient; when the Ni content is too high, it increases alloy cost and increases welding crack sensitivity. Therefore, the Ni content in this invention is controlled within the range of 0.50% to 0.90%.
[0030] Cu: Cu is an important element for improving the corrosion resistance of steel in chlorinated marine environments. Cu enriches at the rust / matrix interface, forming Cu₂O and Cu-containing spinel phases, which improves the density, adhesion, and polarization resistance of the protective rust layer, hindering Cl⁻ diffusion into the matrix. Simultaneously, Cu has a certain solid solution strengthening effect, which is beneficial for the 46kg strength matching of this invention. If the Cu content is too low, the enrichment and barrier effect of the inner rust layer is insufficient; if the content is too high, it easily increases the risk of hot working cracks and copper embrittlement, and may affect weldability. Therefore, the Cu content in this invention is controlled within the range of 0.25%~0.45%.
[0031] Mo: Mo is a key corrosion-resistant element for improving the resistance of steel plates to pitting corrosion, crevice corrosion, and repassivation. In seawater immersion corrosion products, Mo can form MoO3 and molybdate products, filling rust layer pores and inhibiting Cl--induced localized corrosion. Simultaneously, Mo can enhance bainite transformation, promoting the formation of an appropriate amount of bainite under the controlled cooling conditions of 500-550℃ (the red-hot temperature of this invention), thus improving the strength and toughness balance of 46kg grade steel plates. If the Mo content is too low, the inhibition of localized corrosion and microstructure regulation are insufficient; if the content is too high, it easily increases alloy cost and increases the sensitivity to cold cracking in welding. Therefore, the Mo content in this invention is controlled within the range of 0.30%~0.50%. Preferably, 1.05%≤Ni+Cu+Mo≤1.85%, 2.0≤(Ni+Cu) / Mo≤4.5. When the total Ni+Cu+Mo content is below 1.05%, the continuity and repassivation ability of the composite corrosion-resistant rust layer are insufficient; when the total content is above 1.85%, alloy cost and sensitivity to welding cracking increase. When the (Ni+Cu) / Mo ratio is below 2.0, Mo is relatively high, leading to decreased weldability and economy; when it is above 4.5, Mo's inhibitory effect on pitting and crevice corrosion is insufficient. Controlling the above ratio within this range allows for a synergistic balance between Ni stabilizing spinel, Cu enriching the internal rust layer, and Mo repassivating.
[0032] Nb: Nb is an important microalloying element used in this invention for microstructure refinement and performance enhancement. It has a strong affinity for non-metallic elements such as C, N, and O, and can form stable micro-precipitates such as NbC, NbN, or Nb(C,N). During the hot working of steel plates, Nb effectively controls the microstructure of the rolled steel plate by inhibiting austenite grain growth, delaying dynamic recrystallization, and promoting ferrite phase transformation, significantly improving the refinement and uniformity of the microstructure, thereby enhancing the strength and toughness matching level of the steel plate. Especially under the single-pass high reduction rolling and low-temperature homogenization strategy adopted in this invention, NbC and other precipitates can act as grain pinning points, effectively improving rolling stability and controlling the final rolled microstructure morphology. Considering the good stability and grain control ability of Nb in the continuous casting + TMCP process, the Nb content is preferably controlled at 0.040%~0.060% in this invention to give full play to its microalloying refinement and strengthening effect, while avoiding coarsening of precipitates and increased costs due to excessive addition.
[0033] Ti: Ti is a key alloying element in the steel of this invention, mainly used to react in situ with boron (B) during the solidification of molten steel to generate TiB2 reinforcing particles. TiB2 has a high melting point, hexagonal crystal structure, and extremely high elastic modulus (approximately 565 GPa). After being finely dispersed in the matrix, it can significantly improve the overall elastic modulus and specific modulus of the steel plate, meeting the service requirements of high-rigidity materials for large offshore wind power structures. Based on the design specifications of the 46kg-grade structural steel plate of this invention (yield strength ≥ 460 MPa, elastic modulus ≥ 220 GPa), the elastic modulus of the conventional carbon steel matrix (approximately 210 GPa) is increased by at least 10 GPa, introducing a TiB2 reinforcing phase with a volume fraction of approximately 3% or more. The Ti content design needs to comprehensively consider the density and molar composition ratio of TiB2, as well as the in-situ reaction efficiency in the molten steel, taking into account potential reaction losses and element segregation in industrial production, to ensure sufficient TiB2 particle formation, controlled size, and uniform distribution, while avoiding Ti residue or the formation of unfavorable inclusions. Furthermore, Ti in this system also functions as a microalloying strengthener, forming fine precipitates such as TiN and TiC with impurities N and C. During hot working, Ti synergistically inhibits austenite grain growth and promotes grain refinement, thereby improving the uniformity of the steel plate's microstructure and its strength-toughness balance. In summary, Ti in this invention serves as both a core element for strengthening phase formation and a microstructure control function. Its content design needs to achieve an optimal balance between strengthening efficiency and metallurgical stability, preferably controlled within the range of 1.5% to 2.5%.
[0034] B: Boolean element is an essential alloying element for constructing the reinforcing phase TiB2 in the steel plate of this invention. Its main function is to react with Ti in situ during the solidification of molten steel to generate TiB2 reinforcing particles, thereby improving the elastic modulus and specific modulus of the steel plate. TiB2 has a high elastic modulus and excellent thermal stability, and its strengthening effect is closely related to its volume fraction, size, and distribution in the matrix. To achieve the performance target of an elastic modulus ≥220 GPa for the 46 kg grade steel plate of this invention while maintaining good strength and toughness, a TiB2 reinforcing phase with a volume fraction of approximately 3%~4% is introduced. The amount of B added must be synergistically matched with the Ti content. Taking into account the stoichiometry (Ti:B ≈ 1:2), molar mass, and reaction efficiency of TiB2, this invention aims to achieve sufficient TiB2 formation while avoiding residual segregation of Ti and B or the formation of other brittle compounds. This is achieved by controlling the mass ratio of Ti to B within the range of -0.4% ≤ Ti - 2.22 × B ≤ 0.4%, ensuring that TiB2 is formed in situ, with controlled particle size and uniform distribution. This also avoids the precipitation of non-target phases or deterioration of the steel plate's plasticity due to excessive Ti or B. Furthermore, trace amounts of B in steel also strengthen grain boundaries, providing microstructural support for the stable service of materials in marine environments. In summary, B in this invention serves both as a reactive component for the formation of the TiB2 reinforcing phase and as an auxiliary element for regulating the microstructure and properties of the steel plate. Its content design must be closely coordinated with the Ti content, comprehensively considering reaction efficiency, nucleation behavior, and metallurgical compatibility. The preferred content range is 0.6% to 1.2%.
[0035] P (Polyphosphate) is a typical harmful impurity element in steel. During cooling and solidification, it easily segregates in the center of the slab and accumulates at grain boundaries to form a brittle thin film structure, significantly reducing the low-temperature impact toughness and ductility of the steel plate. It also exacerbates the crack sensitivity of the weld heat-affected zone, affecting the weldability of the steel. Although P can improve the corrosion resistance of steel under certain conditions, its weakening effect on fatigue performance and overall ductility and toughness is more significant, making it difficult to use as a corrosion-resistant alloying element in high-strength and toughness structural steels. The steel plate of this invention has been designed to improve corrosion resistance in a fully immersed seawater environment by adding Ni, Cu, and Mo, thus not relying on P for corrosion resistance. To ensure the low-temperature impact performance, ductility, and weld safety of the steel plate, this invention strictly controls the P content to no more than 0.01% to ensure overall service reliability.
[0036] S: S is a typical harmful impurity element in steel, readily reacting with Mn to form low-melting-point MnS inclusions. Especially during hot rolling, these inclusions tend to extend along the rolling direction, forming banded structures that become microcrack initiations under fatigue loads or low-temperature impact conditions, severely impairing the steel plate's fatigue resistance, impact toughness, and thickness-direction (Z-direction) properties. Furthermore, S inclusions are also detrimental to the stability and crack resistance of the subsequent weld zone. To ensure good ductility and toughness in the steel plate, this invention further controls the purity of the molten steel based on a low-Mn design, preferably with an S content ≤0.002%. Under certain non-critical service conditions or without Z-direction property (thickness-direction plasticity) requirements, an S content of ≤0.004% is also acceptable.
[0037] Ca: Ca is a purity and inclusion modifier, mainly used to modify sharp-angled Al2O3 and MnS into spherical-passive calcium aluminate / fine CaS, thereby reducing fatigue crack initiation sites, improving thickness-direction properties, and weld joint reliability. Simultaneously, by reducing high-energy oxide interfaces and micro-cracks, it indirectly improves corrosion fatigue life under full seawater immersion conditions and can alleviate nozzle nodule formation and inclusion tendency in continuous casting. Ca modification can also indirectly optimize in-situ TiB2 precipitation in the Ti-B system by reducing the surface energy and heterogeneous nucleation preference of Al2O3 inclusions, inhibiting TiB2 adsorption growth and agglomeration on oxide surfaces, and reducing residual oxygen through strong deoxidation, thereby improving the effectiveness of Ti in TiB2 formation, resulting in finer and more uniformly distributed TiB2 particles. Ca is not used as a strengthening element and should be strictly controlled in trace amounts. In terms of process, it is preferable to feed Ca at the end of the RH stage after adding Ti and B and soft blowing for 40 seconds, and control the [Ca] / [S] ratio according to [S] linkage to achieve a [Ca] / [S] ratio of 0.8~1.2, and combine it with Als at 0.015%~0.025% to obtain a stable modification effect. Excessive Ca can easily generate coarse CaO / CaS inclusions or bubbles, which can lead to decreased fatigue and corrosion resistance, and increase the risk of nozzle nodule formation and surface defects. Therefore, the present invention preferably controls Ca at 0.0010%~0.0030%.
[0038] Als: As a necessary deoxidizing and grain-refining element added in this invention, the added content is above 0.01%, but exceeding 0.08% can easily cause hot cracking in the cast billet, and at the same time reduce the toughness of the steel. The Als content is controlled between 0.015% and 0.025%.
[0039] The present invention also provides an industrial production method for 46kg-grade offshore wind power steel with high elastic modulus:
[0040] (1) Smelting process: The present invention is smelted according to the designed alloy composition range, using converter or electric furnace smelting, LF refining, and RH vacuum circulation refining.
[0041] During the smelting process, the content of each alloying element and the purity of the molten steel are precisely controlled. In the LF refining stage, dephosphorization is performed until the P content is no higher than 0.01%, desulfurization until the S content is no higher than 0.002%, total oxygen content is controlled below 18 ppm, and nitrogen content is controlled below 0.0030%. Deep degassing via RH ensures that diffusible hydrogen is no higher than 1.5 ppm. Ni, Cu, and Mo elements are added in stages during the LF refining alloying stage, and Ti and B elements are precisely added at the end of the RH process. This ensures that the mass ratio of Ti to B meets the condition -0.4% ≤ Ti - 2.22 × B ≤ 0.4%, so that TiB2 reinforcing particles with an average particle size of no more than 3 μm are generated in situ during the solidification process of the molten steel. Ti and B are added and gently blown with argon for 8-12 minutes. Then, after ≥40 seconds of Ti and B addition, Ca wire is fed in for inclusion modification, transforming sharp-angled Al₂O₃ and MnS into spherical, blunt-shaped calcium aluminate / fine CaS, reducing fatigue crack initiation sites and improving the conditions for uniform TiB₂ particle precipitation. Simultaneously, argon is continuously blown for at least 55 minutes during LF refining to promote homogenization of elements in the molten steel and prevent coarsening of TiB₂ particles, ensuring uniform composition and particle distribution. RH refining lasts ≥35 minutes. At the end of RH refining, the alloy composition and temperature of the molten steel are precisely adjusted, and the superheat at tapping is controlled below 25°C to provide stable metallurgical conditions for subsequent continuous casting processes.
[0042] (2) Continuous casting process: Slab continuous casting process is adopted, with protective pouring throughout the continuous casting process. The slab thickness is 250~300mm, the continuous casting speed is controlled within the range of 0.8~1.0m / min, and the liquid level fluctuation in the crystallizer is controlled within ±3mm. In order to promote the refinement and uniform dispersion of TiB2 reinforcing particles, electromagnetic stirring (M-EMS) is set in the continuous casting crystallizer. The stirring current is preferably controlled at 560~620A and the frequency is 5~7Hz. In the secondary cooling section, solidification end electromagnetic stirring (F-EMS) is used to further optimize the fluidity of molten steel and avoid grain boundary segregation and TiB2 particle agglomeration and coarsening. The preferred current of the solidification end electromagnetic stirring F-EMS in the secondary cooling section is 480~540A and the frequency is 3~5Hz. The secondary cooling section employs a zoned cooling method, with the specific water content in the foot roll section, bending section, and straightening section controlled at 0.30~0.36 L / kg, 0.22~0.29 L / kg, and 0.14~0.19 L / kg, respectively. This is coordinated with the F-EMS system to ensure uniform growth of the solidified shell on the billet, reducing the risk of center segregation, shrinkage cavities, and internal cracks. After the billet exits the mill, a slow cooling device is used to reduce the internal stress gradient, further improving the billet quality and laying the foundation for subsequent controlled rolling and controlled cooling processes.
[0043] (3) Heating process: In order to prevent the billet from overheating during the heating process, a low temperature heating + short time heat preservation process is adopted. Under the premise of ensuring the homogenization of austenite, the original austenite grain size is controlled. The heating temperature is controlled at 1130~1180℃, the total heating time is controlled at 5~6h, and the furnace exit temperature is controlled at 1100~1150℃.
[0044] (4) Rolling process: After heating the continuously cast billet, a three-stage controlled rolling process is adopted. The first stage of rolling starts at 1000~1080℃ and is carried out in the austenite recrystallization temperature zone. The maximum rolling torque is 3100kNm and the cumulative reduction rate is ≥45%, including at least one large reduction pass with a single pass reduction rate of ≥25%. In this stage, the large reduction deformation in the recrystallization zone is used to break the as-cast structure, promote the deformation nuclei of the austenite phase, refine the γ phase and store energy, create conditions for the subsequent γ→α phase transformation, and improve the uniformity of TiB2 reinforcing particles along the thickness direction. The second stage of rolling starts at 860~890℃ and is carried out in the austenite non-recrystallization temperature zone. The average single pass reduction rate is maintained above 20% to provide more nucleation points and increase the nucleation rate under non-recrystallization conditions, further refine the structure and increase the proportion of ferrite. The third stage of rolling begins at a rolling temperature of 780~800℃, and rolling is carried out in the austenite + ferrite two-phase region. The cumulative reduction rate is controlled at 18%~24%, and the target thickness is achieved.
[0045] (5) Straightening process: The rolled steel plate needs to be straightened to improve the flatness of the steel plate and prevent problems such as warping of the steel plate during the cooling process.
[0046] (6) Cooling process: After straightening, the steel plate is placed in a rapid laminar flow cooling system with an average cooling rate of 8-10℃ / s at a temperature of 730-750℃. The reddening temperature is controlled at 500-550℃ to control the composition and size of the phase transformation structure, resulting in a ferrite plus bainite dual-phase structure. After cooling, the steel plate is subjected to slow cooling for ≥32h.
[0047] Through the above-mentioned smelting, continuous casting, and TMCP process control, the uniformity of the final steel plate's microstructure, the grain size of the reinforcing phase, the grain size, and the proportion of each phase are ensured to meet the design requirements. Specifically, the ferrite volume percentage is 75%~85%, the average ferrite grain diameter is <11μm, the TiB2 reinforcing phase particle volume fraction is >3%, the average particle size is <3μm, and the distribution density is 2000~3000 particles / mm². 2 .
[0048] The beneficial effects of this invention are as follows:
[0049] (1) This invention adopts a composition design of low C, Mn + “Ni-Cu-Mo” seawater immersion corrosion resistant alloying + “Ti-B” in-situ precipitation reinforcement phase + Nb microalloying. On the basis of ensuring high ferrite ratio and good plasticity reserve in the low C, low Mn system, the composition is controlled to 1.05%≤Ni+Cu+Mo≤1.85% and 2.0≤(Ni+Cu) / Mo≤4.5 to form a stable and uniform composite corrosion resistant rust layer, and the microstructure is refined by Nb microalloying.
[0050] (2) During the refining and alloying stage, the Ti and B mass ratio is precisely controlled (-0.4%≤Ti-2.22×B≤0.4%) to form fine and dispersed TiB2 particles in situ in the low C-Mn-Ni / Cu / Mo-Nb corrosion-resistant matrix, providing an increase in elastic modulus. The distribution of the reinforcing phase is optimized by combining electromagnetic stirring (M-EMS) in the continuous casting crystallizer and electromagnetic stirring (F-EMS) at the end of the solidification of the secondary cooling section. Combined with the low-temperature homogenization + three-stage controlled rolling + controlled cooling process, the steel plate matrix is finally obtained as a ferrite + bainite dual-phase structure (ferrite volume fraction 75%~85%, average grain size >10 grade), and dispersed TiB2 hard reinforcing particles with a volume fraction greater than 3% are distributed. The average particle size is <3μm and the distribution density is 2000~3000 particles / mm. 2 .
[0051] (3) The microstructure of the steel plate is controlled throughout the entire process of steelmaking electromagnetic stirring (EMS), low temperature homogenization + short time heat preservation continuous casting billet heating, single-pass high reduction rate rolling and Ca inclusion modification, and finally a 46kg grade high elastic modulus medium and thick plate product with strong plasticity, stable toughness and resistance to seawater full immersion corrosion is obtained.
[0052] (4) The steel plate of this invention has an elastic modulus ≥220GPa, yield strength ≥460MPa, tensile strength 550~720MPa, elongation after fracture ≥21%, Charpy impact energy ≥150J at -20℃. Under the condition of 3.5% neutral NaCl solution in the test solution, the steel plate has a full immersion corrosion cycle node set of 168h, 336h, and 504h. The penetration rate (mm / y) of 168h is 0.038~0.056, the penetration rate (mm / y) of 336h is 0.037~0.054, and the penetration rate (mm / y) of 504h is 0.035~0.051. It has high elastic modulus, good elongation, low temperature toughness and resistance to full immersion corrosion in seawater. It is suitable for underwater structures such as floating wind turbine tendon tubes, underwater compartments, and outer plates of pontoons / buoy boxes, and can meet the requirements for long-term safe service in the full immersion environment of seawater. The medium-thick steel plate for large offshore wind power equipment prepared by this invention has high elastic modulus, resistance to full seawater immersion corrosion, good elongation and low temperature toughness, and its comprehensive performance can meet the long-term service conditions of offshore wind power equipment. Attached Figure Description
[0053] Figure 1 This is the metallographic microstructure at the 1 / 4 thickness position of Embodiment 1 of the present invention. Detailed Implementation
[0054] The present invention will be further illustrated below through examples.
[0055] The elemental composition of the wind power steel of this invention, by mass percentage, is as follows: C: 0.035%~0.045%, Si: 0.20%~0.30%, Mn: 0.80%~0.90%, Ni: 0.50%~0.90%, Mo: 0.30%~0.50%, Cu: 0.25%~0.45%, Nb: 0.040%~0.060%, Ti: 1.50%~2.50%, B: 0.60%~1.20%, Ca: 0.0010%~0.0030%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities;
[0056] Furthermore, in the wind power steel, -0.4%≤Ti-2.22×B≤0.4%.
[0057] Furthermore, in the wind power steel, 1.05%≤Ni+Cu+Mo≤1.85% and 2.0≤(Ni+Cu) / Mo≤4.5.
[0058] Furthermore, the microstructure of the wind power steel includes ferrite and bainite, with fine TiB2 hard reinforcing particles uniformly dispersed throughout the steel.
[0059] Furthermore, the ferrite volume percentage is 75%~85%, and the average ferrite grain diameter is <11μm; the TiB2 hard reinforcing particles in the wind power steel have a volume fraction >3%, an average particle size <3μm, and a distribution density of 2000~3000 particles / mm. 2 .
[0060] The steel plate used for offshore wind power has an elastic modulus ≥220GPa, yield strength ≥460MPa, tensile strength 550~720MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥150J, and a steel plate thickness of 20~40mm.
[0061] The embodiments involve smelting, continuous casting, heating, controlled rolling, and controlled cooling according to the component ratio of the technical solution.
[0062] Heating: The continuous casting billet is heated at 1130~1180℃ for a total duration of 5~6 hours;
[0063] Controlled rolling: A three-stage controlled rolling process is adopted after the continuous casting billet is heated;
[0064] The first stage rolling temperature is 1000~1080℃, and the cumulative reduction rate is ≥45%, including at least one large reduction pass with a single pass reduction rate of ≥25%.
[0065] The second-stage rolling temperature is 860~890℃, and the average single-pass reduction rate is ≥20%.
[0066] The third stage rolling temperature is 780~800℃, the cumulative reduction rate is 18%~24%, and the rolling is completed to the target thickness.
[0067] Controlled cooling: After straightening, the steel plate is initially cooled at 730~750℃ and then enters a rapid laminar flow cooling system at a cooling rate of 8~10℃ / s, with a reddening temperature of 500~550℃. After cooling, the steel plate is subjected to slow cooling for ≥32 hours.
[0068] Furthermore, smelting includes converter or electric furnace smelting, LF refining, and RH refining.
[0069] During the LF refining stage, P ≤ 0.01% and S ≤ 0.002% are controlled. Before the RH refining is completed, the total oxygen content in the molten steel is controlled to be ≤ 18 ppm, the nitrogen content to be ≤ 0.0030%, and the diffusible hydrogen content to be ≤ 1.5 ppm.
[0070] During the LF refining and alloying stage, Ni, Cu and Mo elements are added in stages. At the end of the RH stage, Ti and B elements are added and argon is gently blown for 8-12 minutes. Then, after Ti and B are added for ≥40 seconds, Ca wire is fed to carry out inclusion modification. At the same time, the argon blowing time during the refining process is ≥55 minutes.
[0071] RH refining time ≥35min, tapping superheat ≤25℃;
[0072] Furthermore, the continuous casting process also includes electromagnetic stirring technology. The electromagnetic stirring current in the continuous casting crystallizer is 560~620A and the frequency is 5~7Hz. The second cooling section adopts electromagnetic stirring at the solidification end, with an F-EMS current of 480~540A and a frequency of 3~5Hz.
[0073] Furthermore, the secondary cooling section adopts a zoned cooling method, with the specific water content in the foot roller section, bending section, and straightening section controlled at 0.30~0.36L / kg, 0.22~0.29L / kg, and 0.14~0.19L / kg, respectively; the billet is slowly cooled after exiting the machine.
[0074] The present invention provides a method for testing the microstructure and properties of steel used in offshore wind power.
[0075] (1) Statistical method for reinforcing phase: The volume fraction, average size, and distribution density of the TiB2 reinforcing phase in steel were obtained quantitatively through scanning electron microscopy (SEM) images. At magnifications of 5000–10000, more than 10 representative fields of view were randomly selected, with each field of view having a statistical area of not less than 1000 μm. 2 Particle boundaries were identified and automatically counted using image analysis software to obtain the number of particles and their equivalent diameter distribution; volume fraction was calculated from the proportion of the particle's projected area. All results were averaged across all fields of view, and the relative error was limited to ±10% to ensure reliability and repeatability.
[0076] (2) Elastic modulus testing: The method specified in GB / T228.1-2021 or ASTM E111-17 shall be adopted. A standard tensile specimen (parallel length 50 mm, diameter 12.5 mm) in the rolling direction shall be taken and stretched at a loading rate of 2 mm / min under room temperature conditions using an extensometer with an accuracy of 0.5 or higher. The elastic modulus shall be calculated based on the slope of the initial linear segment of the stress-strain curve, and the average value of 3 parallel specimens shall be taken as the result.
[0077] (3) Seawater Immersion Corrosion Resistance Test: This invention uses a full immersion corrosion test to simulate the seawater immersion service environment. The test method is performed in accordance with the ASTM G31 standard guideline, and a 36mm thick Q460MD steel plate is used as a comparative example. The removal of corrosion products and weight loss assessment are performed in accordance with the ASTM G1 standard guideline. The test solution is a 3.5% (mass fraction) NaCl neutral solution, the test temperature is 35±2℃, and the solution is continuously aerated (air) to maintain near-saturation of dissolved oxygen. After pretreatment as specified in ASTM G1, the samples are suspended in an insulating manner and completely immersed in the solution, with no contact between the samples; the liquid-to-solid ratio is ≥20mL / cm³. 2 The solution conductivity and pH were kept stable. Test cycle points were set at 168h, 336h, and 504h. After the test, corrosion products were removed according to the ASTM G1 cleaning / rust removal procedure, and the solution was dried to constant weight. The penetration rate CR (mm / y) was calculated using the ASTM general formula: 87.6 × W / (A × T × ρ), where W is the weight loss (mg) and A is the exposed area (cm²). 2 T represents the exposure time (h), and ρ represents the material density (g / cm³). 3 ).
[0078] The compositions of the steels in the embodiments of the present invention and the comparative steels are shown in Table 1. The main process parameters for smelting and continuous casting of the steels in the embodiments of the present invention are shown in Table 2. The zonal cooling parameters for the secondary cooling section of the continuous casting of the steels in the embodiments of the present invention are shown in Table 3. The main process parameters for heating and the first and second stage controlled rolling of the steels in the embodiments of the present invention are shown in Table 4. The main process parameters for the third stage controlled rolling and controlled cooling of the steels in the embodiments of the present invention are shown in Table 5. The mechanical properties of the steels in the embodiments of the present invention and the comparative steels are shown in Table 6. The seawater full immersion corrosion penetration rate (mm / y) of the steels in the embodiments of the present invention and the comparative steels are shown in Table 7. The microstructure of the steels in the embodiments of the present invention is shown in Table 8.
[0079] Table 1. Composition (wt%) of the steel in the embodiments of the present invention and the comparative steel.
[0080] 1 0.038 0.27 0.84 0.62 0.32 0.42 0.052 1.82 0.80 0.0013 0.021 3.25 0.044 1.36 2 0.043 0.21 0.89 0.78 0.41 0.31 0.045 2.16 0.96 0.0021 0.019 2.66 0.029 1.5 3 0.036 0.29 0.81 0.54 0.30 0.37 0.058 1.58 0.72 0.0016 0.023 3.03 -0.018 1.21 4 0.041 0.24 0.86 0.88 0.48 0.28 0.041 2.34 1.04 0.0023 0.016 2.42 0.031 1.64 5 0.045 0.22 0.82 0.70 0.35 0.45 0.049 1.94 0.88 0.0013 0.025 3.29 -0.014 1.5 6 0.039 0.30 0.90 0.82 0.50 0.33 0.060 2.48 1.12 0.0024 0.020 2.30 -0.006 1.65 Comparative Example 0.121 0.30 1.57 0.50 - - 0.050 0.015 - - 0.035 - - -
[0081] In the steel of this invention embodiment: P: ≤0.01%, S: ≤0.002%, N: ≤0.0030%, O: ≤0.0018%; α=(Ni+Cu) / Mo, β=Ti-2.22×B, γ=Ni+Cu+Mo.
[0082] Table 2 Main process parameters for steel smelting and continuous casting in the embodiments of the present invention.
[0083] 1 56 36.0 1.08 23 250 580 5 500 4 0.8 2 60 38.0 1.11 21 300 610 6 530 5 0.9 3 55 35.5 1.07 24 250 570 6 490 3 0.8 4 62 39.0 1.15 20 300 620 7 540 5 1.0 5 58 37.0 1.03 22 300 590 6 510 4 0.9 6 61 38.5 1.20 21 300 600 7 520 5 1.0
[0084] Table 3. Zoned cooling parameters for the secondary cooling section of continuous casting steel according to embodiments of the present invention.
[0085] 1 0.32 0.24 0.15 2 0.35 0.27 0.18 3 0.31 0.23 0.14 4 0.36 0.28 0.17 5 0.33 0.29 0.19 6 0.34 0.25 0.16
[0086] Table 4. Main process parameters for steel heating and one- and two-stage controlled rolling in the embodiments of the present invention.
[0087] 1 1145 5.2 1035 50 32 884 23 2 1170 5.6 1068 47 28 872 22 3 1135 5.1 1012 52 34 889 24 4 1180 5.8 1076 46 30 865 21 5 1155 5.5 1048 49 27 878 23 6 1165 6.0 1059 51 33 886 22
[0088] Table 5. Main process parameters for three-stage controlled rolling and controlled cooling of steel in the embodiments of the present invention.
[0089] 1 796 776 22 740 8.5 525 34 2 788 774 19 745 9.2 512 36 3 800 778 24 735 8.8 538 32 4 790 771 20 750 9.5 505 38 5 783 775 23 732 8.1 548 35 6 794 779 21 748 9.0 520 37
[0090] Table 6 Mechanical properties of the steels in the embodiments of the present invention and the comparative steels
[0091] 1 28 225 486 610 24 171 2 36 228 503 638 22 164 3 24 223 474 592 25 180 4 40 231 515 655 21 156 5 32 226 492 620 23 168 6 36 229 508 646 22 160 Comparative Example 36 208 469 577 22 154
[0092] Table 7. Seawater full immersion corrosion penetration rate (mm / y) of the steels in the embodiments of the present invention and the comparative steels.
[0093] 1 0.049 0.047 0.045 2 0.043 0.041 0.039 3 0.056 0.054 0.051 4 0.038 0.037 0.035 5 0.041 0.039 0.037 6 0.040 0.038 0.036 Comparative Example 0.088 0.087 0.091
[0094] Table 8. Steel microstructure of embodiments of the present invention
[0095] 1 78 10.6 22 3.3 2.5 2180 2 80 10.1 20 3.6 2.3 2410 3 76 10.8 24 3.1 2.7 2060 4 84 9.6 16 3.8 2.1 2680 5 79 10.4 21 3.5 2.4 2320 6 82 9.9 18 3.9 2.0 2850
[0096] The mechanical properties of the steel in this embodiment of the invention were tested according to GB / T228.1-2021 "Metallic materials, tensile testing - Part 1: Test at room temperature" and GB / T229-2020 "Metallic materials, Charpy impact test method". The elastic modulus was calculated using the method specified in GB / T228.1-2021 or ASTM E111-17, by the slope of the initial linear segment of the stress-strain curve, and the result was taken as the average value of three parallel specimens.
[0097] This invention employs a full immersion corrosion test to simulate a seawater immersion service environment, using a 36mm thick Q460MD steel plate as a comparative example. The test method follows ASTM G31 guidelines, and the removal of corrosion products and weight loss assessment follow ASTM G1 guidelines. The test solution is a 3.5% (mass fraction) neutral NaCl solution, the test temperature is 35±2℃, and the solution is continuously aerated (with air) to maintain near-saturated dissolved oxygen. After pretreatment as specified in ASTM G1, the samples are suspended in an insulated manner and completely immersed in the solution, with no contact between samples; the liquid-to-solid ratio is ≥20mL / cm³. 2 The solution conductivity and pH were kept stable. The test cycle nodes were set at 168h, 336h, and 504h. The penetration rate (mm / y) was calculated using the weight loss method to evaluate the corrosion resistance of the steel plate.
[0098] In this embodiment of the invention, the microstructure of the steel was detected using an optical microscope and a scanning electron microscope (SEM). The ferrite volume fraction and grain size were determined according to GB / T6394-2017. The volume fraction, average size, and distribution density of the TiB2 reinforcing phase particles were obtained through quantitative analysis of SEM images. At least 10 fields of view were randomly selected at 5000–10000x magnification, with each field having a statistical area ≥1000 μm. 2 The results are taken as average values, and the measurement error is controlled within ±10%.
[0099] The offshore wind power steel plate produced using this invention has a ferrite + bainite dual-phase microstructure, wherein the ferrite volume fraction is 75%~85%, the average grain size is >10, and TiB2 hard reinforcing particles with a volume fraction greater than 3% are dispersedly distributed, with an average particle size <3μm and a distribution density of 2000~3000 particles / mm. 2The steel plate of this invention has an elastic modulus ≥220 GPa, yield strength ≥460 MPa, tensile strength 550~720 MPa, elongation after fracture ≥21%, and Charpy impact energy ≥150 J at -20℃. Under the test solution of 3.5% neutral NaCl solution, with full immersion corrosion cycle nodes of 168h, 336h, and 504h, the penetration rate (mm / y) is 0.038~0.056 at 168h, 0.037~0.054 at 336h, and 0.035~0.051 at 504h. It combines high elastic modulus, good elongation, low-temperature toughness, and resistance to full immersion corrosion in seawater. It is suitable for underwater structures such as floating wind turbine tendons, underwater compartments, and outer plates of pontoons / buoy boxes, and can meet the requirements for long-term safe service in full immersion environments in seawater.
[0100] To illustrate the present invention, the present invention has been appropriately and sufficiently described above through embodiments. The above embodiments are only for illustrating the present invention and are not intended to limit the present invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Any modifications, equivalent substitutions, improvements, etc., should be included within the protection scope of the present invention. The patent protection scope of the present invention should be defined by the claims.
Claims
1. A 46kg grade offshore wind power steel with high elastic modulus, characterized in that, The elemental composition of the wind power steel, by mass percentage, is as follows: C: 0.035%~0.045%, Si: 0.20%~0.30%, Mn: 0.80%~0.90%, Ni: 0.50%~0.90%, Mo: 0.30%~0.50%, Cu: 0.25%~0.45%, Nb: 0.040%~0.060%, Ti: 1.50%~2.50%, B: 0.60%~1.20%, Ca: 0.0010%~0.0030%, P: ≤0.01%, S: ≤0.002%, Als: 0.015%~0.025%, with the remainder being Fe and unavoidable impurities.
2. The 46kg grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, In the steel used for wind power, -0.4%≤Ti-2.22×B≤0.4%.
3. The 46kg-grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The steel used in wind power has a content of 1.05%≤Ni+Cu+Mo≤1.85% and a content of 2.0≤(Ni+Cu) / Mo≤4.
5.
4. The 46kg grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The microstructure of the wind power steel includes ferrite and bainite, with TiB2 hard reinforcing particles dispersed throughout the steel.
5. The 46kg grade offshore wind power steel with high elastic modulus according to claim 4, characterized in that, The ferrite volume percentage is 75%~85%, and the ferrite grain diameter is <11μm; the TiB2 hard reinforcing particles in the wind power steel have a volume fraction >3%, an average particle size <3μm, and a distribution density of 2000~3000 particles / mm. 2 .
6. The 46kg-grade offshore wind power steel with high elastic modulus according to claim 1, characterized in that, The steel plate for wind power has an elastic modulus ≥220GPa, yield strength ≥460MPa, tensile strength 550~720MPa, elongation after fracture ≥21%, Charpy impact energy at -20℃ ≥150J, and a plate thickness of 20~40mm.
7. A method for producing 46kg grade offshore wind power steel with high elastic modulus as described in any one of claims 1-6, characterized in that, This includes smelting, continuous casting, heating, controlled rolling, and controlled cooling; Heating: The continuous casting billet is heated at 1130~1180℃ for a total duration of 5~6 hours; Controlled rolling: A three-stage controlled rolling process is adopted after the continuous casting billet is heated; The first stage of rolling starts at a rolling temperature of 1000~1080℃, with a cumulative reduction rate of ≥45%, including at least one large reduction pass with a single pass reduction rate of ≥25%. The second-stage rolling temperature is 860~890℃, and the average single-pass reduction rate is ≥20%. The third stage of rolling begins at a rolling temperature of 780~800℃, with a cumulative reduction rate of 18%~24%, and is rolled to the target thickness. Controlled cooling: After straightening, the steel plate is initially cooled at 730~750℃ and then enters a rapid laminar flow cooling system at a cooling rate of 8~10℃ / s, with a reddening temperature of 500~550℃. After cooling, the steel plate is subjected to slow cooling for ≥32 hours.
8. The method for producing 46kg grade offshore wind power steel with high elastic modulus according to claim 7, characterized in that, Smelting includes converter or electric furnace smelting, LF refining, and RH refining; During the LF refining stage, P ≤ 0.01% and S ≤ 0.002% are controlled. Before the RH refining is completed, the total oxygen content in the molten steel is controlled to be ≤ 18 ppm, the nitrogen content to be ≤ 0.0030%, and the diffusible hydrogen content to be ≤ 1.5 ppm. During the LF refining and alloying stage, Ni, Cu and Mo elements are added in stages. At the end of the RH stage, Ti and B elements are added and argon is gently blown for 8-12 minutes. Then, after Ti and B are added for ≥40 seconds, Ca wire is fed to carry out inclusion modification. At the same time, the argon blowing time during the refining process is ≥55 minutes. RH refining time ≥35min, tapping superheat ≤25℃.
9. A method for producing 46kg-grade offshore wind power steel with high elastic modulus according to claim 7, characterized in that, The continuous casting process also includes electromagnetic stirring technology. The electromagnetic stirring in the continuous casting crystallizer is M-EMS with a current of 560~620A and a frequency of 5~7Hz. The solidification end electromagnetic stirring in the second cooling section is F-EMS with a current of 480~540A and a frequency of 3~5Hz.
10. A method for producing 46kg-grade offshore wind power steel with high elastic modulus according to claim 7, characterized in that, The secondary cooling section adopts a zoned cooling method, with the specific water content in the foot roller section, bending section, and straightening section controlled at 0.30~0.36L / kg, 0.22~0.29L / kg, and 0.14~0.19L / kg, respectively; the billet is slowly cooled after exiting the machine.
Citation Information
Patent Citations
Offshore wind power steel with yield strength being larger than or equal to 460MPa and manufacturing method
CN108265226A
A steel for offshore wind power with high fracture toughness and low aging sensitivity and its production method
CN111809117B
Steel for offshore wind power flange and preparation method
CN113913690A
A high-elastic modulus age-hardening high-speed steel material and its preparation method
CN114686783B